Socialization of Zoom Application Utilization for Making a Learning Presentation in Video Form - Retna Ningsih; Dewi Mustari; Reko Syarif Hidayatulloh (Institut Teknologi Nasional, Bandung, 2021)
Learning is a process of student interaction with teachers and learning resources in a learning environment. The article clearly states that learning is a process of interaction between teachers (educators) and students (students). During this pandemic, all learning processes are carried out remotely. Because face-to-face learning in class cannot be carried out as a result of the highly contagious corona virus outbreak. The selection of the right learning media must pay attention to and adjust the needs of the subject matter so that the media functions as a tool that can increase understanding and interest in learning. Zooming presentation learning media is one of the newest applications that has a fresh, unique, attractive appearance and has sophistication in zooming in and out and can combine videos, images and animations. With this community service, it is hoped that it can help the problems of teachers at Darul Faizin High School regarding online learning problems. So that this socialization can be a solution in providing learning materials to students.